2019
DOI: 10.5395/rde.2019.44.e15
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of fracture strength testing for endodontically treated teeth: a finite element analysis study

Abstract: Objectives The aim of this study was to investigate whether the diameter and direction of the plunger and simulation of the periodontal ligament (PDL) affected the stress distribution in endodontically treated premolars. Methods A fracture strength test was simulated via finite element analysis. A base model was set up, and the following parameters were modified: plunger diameter (3 mm vs. 6 mm), plunger direction (vertical vs. 135° angular to the central fossa), and PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Other parameters could also affect the results of the ex vivo biomechanical tests, such as the diameter of the spherical stainless-steel antagonist, the direction and the speed of the applied force and whether or not the periodontal ligament is simulated. Indeed, according to different studies [50,51], the direction of the spherical antagonist would affect the distribution and accumulation of stresses on the crown and the roots of a teeth. In fact, an angular direction could lead to increased stresses in the roots, while an axial direction would not lead to any significant stress accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other parameters could also affect the results of the ex vivo biomechanical tests, such as the diameter of the spherical stainless-steel antagonist, the direction and the speed of the applied force and whether or not the periodontal ligament is simulated. Indeed, according to different studies [50,51], the direction of the spherical antagonist would affect the distribution and accumulation of stresses on the crown and the roots of a teeth. In fact, an angular direction could lead to increased stresses in the roots, while an axial direction would not lead to any significant stress accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the direction of the chewing forces, an angular application in a fracture resistance test is closer to a real clinical situation. As for the diameter of the sphere, this can lead to stress variations on the crown contact area but not at the root level [51]. In fact, the diameter seems to be a less important parameter.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that root fracture chances increased with increased tapering of instruments, and excessive radicular dentin removal. [ 1 2 ] The direction and position of root fracture can be influenced by root canal shape, dentin thickness, and external root morphology. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Finite element analysis was used to identify the factors that influence the susceptibility of fracture. [ 1 ] Considering this, we attempted the present study to determine the stress distribution in three tapers of preparation of root canal with the help of finite element analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The direction and location of the loading tip as well as the shape and the diameter may influence the results of the test. Usually, the direction of the applied forces, used in this in vitro test, are axial on both buccal and palatal cusps with an inclination of 30/45°, and this could sensibly influence the outcome of the test [ 6 ]. The periodontal ligament is an anatomical structure able to distribute the occlusal load thanks to its fibers.…”
Section: Introductionmentioning
confidence: 99%